Public relations writing : the essentials of style and format - Bivins, Thomas H. 1947- (NTC/Contemporary, 1999)
This book is about: Writing for public relations; Planning your message; Choosing the right message and medium; Ethical and legal issues in public relations writing; Media relations and placement; News releases and backgrounders; Annual reports...